Dorsal Root Ganglion Stimulation Normalizes Measures of Pain Processing in Patients with Chronic Low‐Back Pain: A Prospective Pilot Study using Quantitative Sensory Testing. Issue 5 (28th January 2021) - Chapman, Kenneth B.; van Roosendaal, Bert‐Kristian; Yousef, Tariq A.; Vissers, Kris C.; van Helmond, Noud
Abstract: Background: Dorsal root ganglion stimulation (DRG‐S) is used as a treatment for chronic low‐back pain (CLBP), although its underlying mechanisms remain elusive. CLBP patients have been found to have reduced mechanoreceptive perception, reduced endogenous analgesia, as well as deep‐tissue hyperalgesia when compared with healthy controls. Using quantitative sensory testing (QST), we studied if DRG‐S in CLBP patients results in changes in pain processing. Methods: Quantitative sensory testing was performed in patients before trial implantation of a DRG‐S system for CLBP and just before the trial lead removal or at 1‐month follow‐up after the permanent implant. We determined the pressure pain threshold (PPT) and mechanical detection threshold (MDT) at the most painful lower‐back location. PPT was also measured on the contralateral shoulder as a control. We obtained a measure of endogenous inhibitory pain modulation using conditioned pain modulation (CPM). Results: We enrolled 11 patients (60 ± 16 years). Pain decreased from 8.5 ± 1.0 at baseline to 2.0 ± 1.5 on a 0‐10 numerical rating scale with DRG‐S ( P < 0.01). From baseline to with DRG‐S, PPT on the most painful location on the low back increased from 28.7 ± 13.6 to 43.4 ± 17.2 N/cm 2 ( P < 0.01). MDT on the same location decreased from 8.1 ± 10.4 to 3.4 ± 4.7 mN ( P = 0.07). PPT on the control location and CPM did not change significantly. Conclusions: Our results suggest that DRG‐S in CLBP patients reduces deep‐tissue hyperalgesia in the low back, while improving mechanoreceptive perception. These changes in both neuropathic and nociceptive components of CLBP were accompanied by clinical improvements in pain and function.